Definition 1: g + H
Let g + H = { g + h such that h ∈ H }.
Example 1.1:
Let G be the set { 0, 1, 2, 3 }
Let H be the set { 9, 10, 11 }
Then:
0 + H = { 9, 10, 11 }
1 + H = { 10, 11, 12 }
2 + H = { 11, 12, 13 }
3 + H = { 12, 13, 14 }
Definition 2: coset of H in G
The set g + H is a coset if and only if there exists a group G such that g ∈ G and H is a subgroup of G.
Note: Technically, definition 3 above describes a left coset. A coset can also be defined as H + g which is called a right coset. The notation of g + H defines a coset based on addition. Cosets can also be defined on multiplication and represented as gH or Hg.
Example 2.1:
Let G = the set of integers Z
Let H = 2Z = the set of even integers
1 ∈ Z
1+H = odd integers = { ... -3, -1, 1, 3, ... }
Example 2.2: Cyclic Group Z4
Z4 = { 0, 1, 2, 3}
It is a group since:
(1) Closure
Since Z4 is always modulo 4, it is clear that that operation of addition is closed (for example: 3 + 2 = 1)
(2) Associativity
For any elements a,b,c ∈ Z4, (a + b) + c = a + (b + c)
(3) Identity Element
0 is the identity element
(4) Inverse Element
Since it is modulo 4, each element has an inverse: 0+0=0, 1+3=0, 2+2=0
Let H = { 0 , 2 }
H is a subset and H is itself a group since:
(1) It has closure: 0+2=2, 0+0=0, 2+2=0
(2) It has associativity.
(3) It has a identity element: 0
(4) From #1, it is clear that each element is its own inverse.
From Z4 and H, there are 2 distinct cosets:
0 + H = { 0, 2}
1 + H = { 1, 3}
2 + H = { 2, 0} = 0 + H
3 + H = { 3, 1} = 1 + H
Lemma 1:
For the coset H in G:
For all a,b ∈ G:
a + H = b + H if and only if a - b ∈ H
Proof:
(1) Assume that a + H = b + H
(2) So, for all x ∈ (a + H) → x ∈ (b + H)
(3) a ∈ a + H, b ∈ b + H [since H is a group and therefore 0 ∈ H]
(4) a ∈ b + H [follows directly from step #2]
(5) Let c = a - b
(6) b + c ∈ b + H [since b + c = a and a ∈ b + H]
(7) So c ∈ H [from step #6 and Definition 3 above]
(8) Assume that (a-b) ∈ H
(9) Assume that x ∈ a + H
(10) Let y = x - a
(11) y ∈ H [since x = a + y]
(12) y + (a - b) ∈ H since H is a group
(13) x - b ∈ H [since y + (a - b) = (x - a) + (a - b) = x - b]
(14) Then x ∈ b + H since [b + x-b = x]
(15) We can make the same argument if x ∈ b + H so this shows that a + H = b + H.
QED
Lemma 2:
For the coset H in G:
a ∈ H → a + H = H
Proof:
(1) Assume that a ∈ H
(2) Assume that x ∈ a + H
(3) Then there exists h such that x = a + h where h ∈ H [See Definition 1 above]
(4) But if a ∈ H and h ∈ H, then a + h ∈ H. [since H is a group, see Definition 2 above and the Closure property of groups]
(5) So x ∈ H
(6) Assume that x ∈ H
(7) Let b = x - a
(8) Since a ∈ H, it follows that -a ∈ H [See Definition 2 above and the Inverse property of groups]
(9) Since x ∈ H and -a ∈ H, it follows that b ∈ H [from the Closure property of groups]
(10) So then, x ∈ a + H [since b ∈ H and x = a + b from Definition 1 above]
QED
Reference
- Jean-Pierre Tignol, Galois' Theory of Algebraic Equations, World Scientific, 2001
No comments :
Post a Comment